The long noncoding RNA THBS1-AS1 promotes cardiac fibroblast activation in cardiac fibrosis by regulating TGFBR1 - Zhou, Junteng; Tian, Geer; Quan, Yue; Kong, Qihang; Huang, Fangyang; Li, Junli; Wu, Wenchao; Tang, Yong; Zhou, Zhichao; Liu, Xiaojing (JCI insight, 2023)
Cardiac fibrosis is associated with an adverse prognosis in cardiovascular disease that results in a decreased cardiac compliance and, ultimately, heart failure. Recent studies have identified the role of long noncoding RNA (lncRNA) in cardiac fibrosis. However, the functions of many lncRNAs in cardiac fibrosis remain to be characterized. Through a whole-transcriptome sequencing and bioinformatics analysis on a mouse model of pressure overload-induced cardiac fibrosis, we screened a key lncRNA termed thrombospondin 1 antisense 1 (THBS1-AS1), which was positively associated with cardiac fibrosis. In vitro functional studies demonstrated that the silencing of THBS1-AS1 ameliorated TGF-β1 effects on cardiac fibroblast (CF) activation, and the overexpression of THBS1-AS1 displayed the opposite effect. A mechanistic study revealed that THBS1-AS1 could sponge miR-221/222 to regulate the expression of TGFBR1. Moreover, under TGF-β1 stimulation, the forced expression of miR-221/222 or the knockdown TGFBR1 significantly reversed the THBS1-AS1 overexpression induced by further CF activation. In vivo, specific knockdown of THBS1-AS1 in activated CFs significantly alleviated transverse aorta constriction-induced (TAC-induced) cardiac fibrosis in mice. Finally, we demonstrated that the human THBS1-AS1 can also affect the activation of CFs by regulating TGFBR1. In conclusion, this study reveals that lncRNA THBS1-AS1 is a potentially novel regulator of cardiac fibrosis and may serve as a target for the treatment of cardiac fibrosis.